2013
DOI: 10.1063/1.4793581
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermal conductivity, viscosity, and electrical conductivity of graphene based nanofluids

Abstract: Stable and well dispersed functionalized graphene–ethylene glycol (EG) + distilled water nanofluids having graphene nano-sheets (GnS) volume concentration between 0.041 and 0.395 vol. % are prepared without any surfactant. Graphene nano-sheets are prepared from high purity graphite powder by Hummers method followed by exfoliation and reduction by hydrogen gas. Thus, obtained hydrogen exfoliated graphene (HEG) is then functionalized using acid. The graphene nano-sheets are characterized using XRD, TEM, Raman sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
94
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(111 citation statements)
references
References 35 publications
9
94
3
Order By: Relevance
“…[26][27][28][29][30][31] Past work has shown that the steady shear viscosity ( , ) of nanofluids typically decreases with increasing temperature at a fixed shear rate. [32][33][34][35][36][37] Although the viscosity of suspensions has been extensively studied in the literature, 21,[37][38][39][40][41][42] there have been few studies that focus on thermal effects on the macroscopic suspension viscosity when the volume loadings pass from the dilute regime into the percolated regime. In this work, we measure the thermal conductivity and viscosity of graphite suspensions as a function of temperature and volume fraction, focusing on the percolation behavior.…”
mentioning
confidence: 99%
“…[26][27][28][29][30][31] Past work has shown that the steady shear viscosity ( , ) of nanofluids typically decreases with increasing temperature at a fixed shear rate. [32][33][34][35][36][37] Although the viscosity of suspensions has been extensively studied in the literature, 21,[37][38][39][40][41][42] there have been few studies that focus on thermal effects on the macroscopic suspension viscosity when the volume loadings pass from the dilute regime into the percolated regime. In this work, we measure the thermal conductivity and viscosity of graphite suspensions as a function of temperature and volume fraction, focusing on the percolation behavior.…”
mentioning
confidence: 99%
“…As indicated by many experiments, the effective electrical conductivity of nanofluids may increase by orders of magnitude by adding a little amount of nanoparticles [61,62]. Previous studies have suggested various models [63][64][65][66] for the effective electrical conductivity of nanofluid, but none of them always provides good predictions.…”
Section: Lorentz Forcementioning
confidence: 99%
“…Previous studies have suggested various models [63][64][65][66] for the effective electrical conductivity of nanofluid, but none of them always provides good predictions. Therefore, in this paper, based on the literature review [59][60][61][62][67][68][69], we consider σ n f = 4.0 S/m (a constant).…”
Section: Lorentz Forcementioning
confidence: 99%
“…The electrical conductivity requirement, which is as low as 1.5 to 2 S/cm [39] and 5 S/cm at 20 C [37], needs to be maintained over time. A few researchers have investigated the effect of electrical conductivity on various types of nanofluids [40][41][42][43][44][45][46][47][48][49][50][51]. Wong and Kurma [40] studied the effect of volume concentration on the electrical conductivity of Al 2 O 3 nanofluid.…”
Section: Challenges Of Nanofluids In Pemfc Electrical Conductivitymentioning
confidence: 99%